Legacy and alternative per- and polyfluoroalkyl substances in the U.S. general population: Paired serum-urine data from the 2013–2014 National Health and Nutrition Examination Survey. (October 2019) - Calafat, Antonia M.; Kato, Kayoko; Hubbard, Kendra; Jia, Tao; Botelho, Julianne Cook; Wong, Lee-Yang
Abstract: Concerns are heightened from detecting environmentally persistent man-made per - and polyfluoroalkyl substances (PFAS) in drinking water systems around the world. Many PFAS, including perfluorooctane sulfonate (PFOS) and perfluorooctanoate (PFOA), remain in the human body for years. Since 1999–2000, assessment of exposure to PFOS, PFOA, and other select PFAS in the U.S. general population has relied on measuring PFAS serum concentrations in participants of the National Health and Nutrition Examination Survey (NHANES). Manufacturers have replaced select chemistries ("legacy" PFAS) with PFAS with shorter biological half-lives (e.g., GenX, perfluorobutanoate [PFBA]) which may efficiently eliminate in urine. However, knowledge regarding exposure to these compounds is limited. We analyzed 2682 urine samples for 17 legacy and alternative PFAS in 2013–2014 NHANES participants ≥6 years of age. Concentrations of some of these PFAS, measured previously in paired serum samples from the same NHANES participants, suggested universal exposure to PFOS and PFOA, and infrequent or no exposure to two short-chain PFAS, perfluorobutane sulfonate and perfluoroheptanoate. Yet, in urine, PFAS were seldom detected; the frequency of not having detectable concentrations of any of the 17 PFAS was 67.5%. Only two were detected in >1.5% of the population: PFBA (13.3%) and perfluorohexanoate (PFHxA, 22.6%); the 90th percentile urine concentrations were 0.1 μg/L (PFBA), and 0.3 μg/L (PFHxA). These results suggest that exposures to short-chain PFAS are infrequent or at levels below those that would result in detectable concentrations in urine. As such, these findings do not support biomonitoring of short-chain PFAS or fluorinated alternatives in the general population using urine, and highlight the importance of selecting the adequate biomonitoring matrix. Highlights: No detectable extensive exposure to alternative PFAS in the U.S. general population Choice of matrix influences the success of biomonitoring exposure assessments Serum levels are best for biomonitoring of PFAS regardless of their biopersistence